Metaphysics in the Epistemology : A Critical Analysis of Islamic and Western Philosophical tradition - Lukman Atmaja; Ridho Ramazani Bin Cecep Mustopa (Afkaruna: Indonesian Interdisciplinary Journal of Islamic Studies, 2020)
Western epistemology was greatly influenced by Greek philosophical ideas. In the course of history, Epistemology has been dominated by patterns of thought that are rational, secular and free from religious values and beliefs. History shows that the Western Epistemology turned into a large school that became dominant: in the form of rationalism, empiricism, criticism, and intuition. Although it has various methods and approaches to acquire knowledge, in principle the building and its foundation have the same way of thinking that comes from a philosophy that upholds the mind and also relies on human sensory abilities. The West denies revelation as a source of knowledge and for Islam, revelation is the highest source of knowledge. Authentic revelation is the Qur'an and Hadith. The result of this paper shows Western epistemology has a foundation and roots that are based on philosophical thinking that is far from the touch of religious values. Western epistemology in its manifestations is then limited to the acquisition of knowledge about the visible world such as sensory nature and not touching on other realms. Western epistemology focuses more on reason and senses as the main source of science, dichotomization, anthropocentrism, opposition to the spiritual dimension, relentless uncertainty, secularization, desacralization, and empiricism. While tthe Islamic epistemology views both sensory and metaphysical objects and recognizes the three sources of knowledge at once namely senses, reason, intuition. Each of these sources has different levels of ability so they cannot be separated and must be used proportionally. The object of knowledge in Islam is not only empirical, but also metaphysical. The source of knowledge in Islam is also different from Western epistemology. If the West only recognizes the senses and ratios, then in the Muslim view, knowledge comes from God obtained through: the senses are healthy, khabar sadiq, and intuition.